2020
DOI: 10.18502/jovr.v15i2.6739
|View full text |Cite
|
Sign up to set email alerts
|

Orthokeratology in Moderate Myopia: A Study of Predictability and Safety

Abstract: Purpose: Literature is relatively silent on safety profile and predictability of orthokeratology lenses in terms of myopia correction and prevention of further progression, especially in semi-tropical countries; this study was designed to fill this gap. Methods: This prospective, intervention case series enrolled 30 eyes of 30 patients with myopia up to –5.5 diopters (D). Patients were randomized into two groups of 15 each; the study group was prescribed overnight orthokeratology (OK) lenses, while the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…As the refractive target increased, both the central and peripheral corneal stress responses increased significantly, especially in the corneal center. Although the FDA or other health authorities approve the use of ortho-k treatment in myopia up to −6.00 D in some lens designs, the safest and most successful outcome will be achieved for those patients with lower baseline levels of myopia ( Mika et al, 2007 ; Liu and Xie, 2016 ; Singh et al, 2020 ; Hu et al, 2021 ). Therefore, for patients with high myopia or for doctors who used to increase the target degrees, more attention must be paid to the possible side effects of the ortho-k lens wear, such as damage to the integrity of the cornea, since those lenses are designed with increased compressive pressure.…”
Section: Discussionmentioning
confidence: 99%
“…As the refractive target increased, both the central and peripheral corneal stress responses increased significantly, especially in the corneal center. Although the FDA or other health authorities approve the use of ortho-k treatment in myopia up to −6.00 D in some lens designs, the safest and most successful outcome will be achieved for those patients with lower baseline levels of myopia ( Mika et al, 2007 ; Liu and Xie, 2016 ; Singh et al, 2020 ; Hu et al, 2021 ). Therefore, for patients with high myopia or for doctors who used to increase the target degrees, more attention must be paid to the possible side effects of the ortho-k lens wear, such as damage to the integrity of the cornea, since those lenses are designed with increased compressive pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, complications in children were not only less frequent, but also less severe than in adults, even accounting for the higher baseline SE in children. It has been suggested that children may benefit from parental oversight with regards to contact lens care and maintenance, and may be more motivated than adults for this particularly demanding modality of lens wear [10,12]. In addition, better tear film integrity and corneal endothelium response in children may also help to explain these findings.…”
Section: Tablementioning
confidence: 99%
“…Research on the efficacy and predictability of ortho-k is commonly conducted within a relatively short time frame, given that refraction stability is reached between seven and 30 days, depending on target refraction and age of patients, with younger patients showing a more rapid corneal response [8][9][10][11][12]. Conversely, studies on the safety of orthokeratology have focussed mainly on children using their lenses for myopia control, describing their findings in terms of incidence, with limited information on the predominant moment of occurrence of each type of adverse effect within the course of the ortho-k treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There is also strong evidence that myopia progression can be significantly reduced by a range of interventions, the most effective being the use of atropine, 14 , 15 , 16 , 17 , 18 , 19 followed by orthokeratology (OK) 20 , 21 , 22 , 23 and peripheral defocus modifying CLs. 24 , 25 , 26 , 27 , 28 , 29 , 30 Despite the good results reported for these treatments, not all study participants responded in the same way.…”
Section: Introductionmentioning
confidence: 99%